Pengaruh Tingkat Efisiensi, Risiko Kredit, dan Tingkat Penyaluran Kredit pada Profitabilitas - Dewi, Ni Putu Intan Puspita; Ariyanto, Dodik (E-Jurnal Akuntansi, 2018)
Profitability is a very important thing required by the company to ensure whether the targeted profit in some period has been achieved. Profitability reflects the good performance of the company. The level of profitability is reflected in the company's earnings. Banks need to maintain high profitability, emerging business prospects, and distribute dividends well for good performance. The purpose of this study is whether BOPO, NPL, and LDR effect on profitability (ROA) at private banking companies in Indonesia Stock Exchange 2014-2016. This research was conducted at private banking companies registered in Indonesia Stock Exchange 2014-2016. The number of samples taken as many as 34 companies, with purposive sampling method. Analysis technique of this research use multiple linear regression analysis. The results of this study indicate that the level of credit disbursement has a positive effect on profitability. Then the level of efficiency and credit risk negatively affect profitability. Keywords: NonPerforming Loan, Loan to Deposit Ratio, Profitability, BOPO, Bank.